Structural changes in periodontium of rats exposed to a low concentration of hydrogen sulfide for 50 days. (August 2016) - Yeler, Defne Yalcin; Hocaoglu, Turgay; Koraltan, Melike; Aydin, Murat; Gul, Mehmet; Gul, Semir
The aim of the present study was to investigate the effect of H2 S inhalation at a low concentration (at human equivalent dose of pathologic halitosis) on rat periodontium over a long term (50 days). The threshold level of pathologic halitosis perceived by humans at 250 ppb of H2 S was converted to rat equivalent concentration (4.15 ppm). Rats in the experimental (H2 S) group (n = 8) were exposed to H2 S continuously but not the control rats (n = 8). After 50 days, periodontal tissue samples were taken from the mandibular first molar region and examined histopathologically to determine inflammatory cell infiltration (ICI), osteoblastic activities, number of osteoclasts, and resorption lacunae. Sulcular epithelium layer destruction was observed in the H2 S group. Frequency of ICI was significantly higher in the H2 S group compared to the control group ( P <0.05). The number of osteoclasts were found significantly higher in the H2 S group (34.28 ± 3.28) compared to the control group (8.85 ± 1.85) ( P <0.05) and the number of resorption lacunae were also higher in the cementum tissue (6.1 ± 2.4) and alveolar bone (3.8 ± 1.5) versus their corresponding control groups (1.6 ± 0.5 and 1.4 ± 0.5, respectively) ( P <0.05). There were no statistically significant differences between the two groups with regard to osteoblastic activity. H2 S inhalation induces inflammatory changes in the periodontium as well as resorption of the alveolar bone and cementum tissue in rats. These histopathologic changes in periodontal tissues support the idea that long-term H2 S inhalation may have a destructive effect on periodontal tissues.